PENGAWASAN TERHADAP PRAMUWISATA DI PROVINSI BALI - I Ketut Suparta (University of Udayana, 2013)
This research is based on a gap that happened in arranging tour guides in Bali in which there are norms conflict between the regional regulation of Bali Province Number 5 Year 2008 on Tour Guide and the Regulation of Cultural and Tourism Minister Number: PM.92/HK.501/MKP/2010 on The Registration Procedure of Tour Guides Business which causes the Government of Bali Province doubtful in doing the authority of controling. In this research is discussed two problem namely the authority of Bali Province Government in arranging the tour guides business and controlling the tour guides. From the research which is conduct with statute approach and the law concept analysis approach that is analyzed by systematization, evaluation, argumentation and description method, it is known that the Bali Province Government has attribution authority which is strict for arranging the tour guides business and this matter implies on the authority to conduct control that includes law and administration, technical ability and tour guides behavior. Since regional regulation made by the autonomous government structure with autonomous autorithy then the regulation that arranges specified authority for that region remains valid.